1999
DOI: 10.2527/1999.7751258x
|View full text |Cite
|
Sign up to set email alerts
|

Heat energy for growing goats and sheep grazing different pastures in the summer.

Abstract: Angora goat, Spanish goat, and Suffolk x Rambouillet sheep wethers (20 of each type; 30.4+/-.57, 31.3+/-.93, and 32.4+/-1.08 kg BW for Angora goats, Spanish goats, and sheep, respectively) were used to investigate influences of animal type and two grass-based pasture treatments on heat energy during summer grazing (mid-August through September in Oklahoma). The improved pasture treatment consisted of .7-ha paddocks primarily of Old World bluestem and johnsongrass, whereas the native pasture treatment entailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Outro aspecto importante foi a maior participação de GORD na composição da costela dos animais terminados em pasto de capim-aruana e capim-tanzânia, que não diferiram entre si (P>0,05), em relação ao capim-andropogon (P<0,05). A gordura está diretamente relacionada à oferta energética da dieta e tem importante função na conformação, na proteção e nas características organolépticas da carcaça e de seus cortes (Poppi & McLennan, 1995;Herselman et al, 1999). Assim, as variedades tanzânia e aruana utilizadas na alimentação dos ovinos foram determinantes do melhor acabamento de carcaça em detrimento àquelas obtidas com capim-andropogon, resultados confirmados também pela análise química da 12 a costela.…”
Section: Resultsunclassified
“…Outro aspecto importante foi a maior participação de GORD na composição da costela dos animais terminados em pasto de capim-aruana e capim-tanzânia, que não diferiram entre si (P>0,05), em relação ao capim-andropogon (P<0,05). A gordura está diretamente relacionada à oferta energética da dieta e tem importante função na conformação, na proteção e nas características organolépticas da carcaça e de seus cortes (Poppi & McLennan, 1995;Herselman et al, 1999). Assim, as variedades tanzânia e aruana utilizadas na alimentação dos ovinos foram determinantes do melhor acabamento de carcaça em detrimento àquelas obtidas com capim-andropogon, resultados confirmados também pela análise química da 12 a costela.…”
Section: Resultsunclassified
“…Similarly, sheep spent a greater portion of time grazing on pastures which had high levels of soluble carbohydrates (Birrell, 1989), which are abundant in succulent species, such as P. afra, as a result of their crassulacean acid metabolism (Borland et al, 2009). Herselman et al (1999) found that Angora goats that grazed on pasture with a high content of browse had higher heat energy, grazed for longer and took more steps per unit of time spent grazing than did goats that grazed on grass pasture. Our goats on the intact site consumed a high proportion of browse and succulent species such as P. afra (Milne, 2008) and so may have foraged for longer, resulting in higher activity levels than goats that inhabited the transformed site.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been previously applied mostly in humans. Only, limited information is available on the applicability of the 13 C bicarbonate dilution technique in ruminants (Herselman et al, 1999;Junghans et al, 1997). In pasture systems or other free ranging systems of land use energy requirements of grazing animals are affected by a range of different environmental factors which can not be easily simulated in respiration chambers commonly used to derive energy expenditure.…”
Section: Introductionmentioning
confidence: 99%